Statistical mechanics of phase–space curves - Rocca, Mario Carlos (2014)
We study the classical statistical mechanics of a phase–space curve. This unveils a mechanism that, via the associated entropic force, provides us with a simple realization of effects such as confinement, hard core, and asymptotic freedom. Additionally, we obtain negative specific heats, a distinctive feature of self-gravitating systems, and negative pressures, typical of dark energy.